The Philippine islands, 1493-1803 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the beginning of the nineteenth century, Volume XV, 1609 - Blair, Emma Helen 1911; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908 (A.H. Clark Co., 1904)
the first installment of Dr. Antonio de Morga's Sucesos de las Islas Filipinas. Events here described cover the years 1493-1603, and the history proper of the islands from 1565. Morga's work is important, as being written by a royal official and a keen observer and participator in affairs. Consequently, he touches more on the practical everyday affairs of the islands, and in his narrative shows forth the policies of the government, its ideals, and its strengths and weaknesses. His book is written in the true historic spirit, and the various threads of the history of the islands are followed systematically. As being one of the first of published books regarding the Philippines, it has special value. Political, social, and economic phases of life, both among the natives and their conquerors, are treated. The futility of the Spanish policy in making external expeditions, and its consequent neglect of internal affairs; the great Chinese question; the growth of trade; communication with Japan; missionary movements from the islands to surrounding countries; the jealous and envious opposition of the Portuguese; the dangers of sea-voyages: all these are portrayed vividly, yet soberly. Morga's position in the state allowed him access to many documents, and he seems to have been on generally good terms with all classes so that he readily gained knowledge of facts. The character of Morga's work and his comprehensive treatment of the history, institutions, and products of the Philippines, render possible and desirable the copious annotations of this and the succeeding volume. These annotations are contributed in part by those of Lord Stanley's translation of Morga, and those of Rizal's reprint, while the Recopilación de leyes de Indias furnishes a considerable number of laws.